Pertalian antara pengalaman masteri dengan efikasi kendiri guru: regresi-meta kajian keratan lintang = The relationship between teachers' mastery experience and teacher self-efficacy: A meta-regression of cross-sectional studies - Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari; Nordin, Abd Razak; Ibrahim, Mohd Burhan; Othman, Joharry (Universiti Utara Malaysia Press, 2017)
This study is an attempt to gather and investigate in depth information on Malaysian university students’ use of the English language in their daily interactions. Essentially, it is a qualitative phenomenological study that utilizes the interview as a tool to gather information from undergraduates of a Malaysian public university based in the Klang valley. Nine students were enquired upon the extent to which English language is used in their daily interactions and challenges that they faced in using the language. Analysis done led to five main themes that represented the pattern of their English language usage. The themes found were indicative that the uses of English language in interactions were (1) limited to needs and situation, (2) based on location and purpose, (3) affected by low self efficacy and language skills (4) strong affective barriers and (5) unsupportive social environment. It could be said that the findings can act as an eye opener for definitive actions to be taken to improve EL interaction amongst Malaysian undergraduates towards the fulfillment of the Malaysia Education Blueprint (MEB-HE) 2015-2025 (Higher Education) aspirations.